Improved chemiluminescence behavior of Cu-etched sulfur quantum dots for Rizatriptan sensitive assay - Sima Mojarrad; Tooba Hallaj; Abdolhossein Naseri; Mohammad Amjadi; Aligholi Niaei (Journal of Analytical Science and Technology)
Abstract Altering the electronic structure and surface functional groups of the pure-elemental quantum dots by heteroatom doping is a relatively new approach to enhance the intensity of the weak chemiluminescence (CL) systems and fabricate the more sensitive sensors for the determination of the analytes. The current study is focused on improving the CL behavior of sulfur quantum dots (SQDs) via etching them by cooper ion (Cu2+) to sensitize the well-known Pyrogallol/IO4 CL system for determination of the anti-migraine compound Rizatriptan in real samples based on its quenching effect on the CL of the system. The SQDs were synthesized by a simple hydrothermal method and etched using Cu2+ to manipulate their optical properties and fluorescence quantum yield. The resulting Cu-etched SQDs (Cu-SQDs) were characterized by TEM, FT-IR, and UV–Vis. A significant enhancement of 150 and 300-fold in the CL intensity of the Pyrogallol/IO4 system was observed upon application of SQDs and Cu-SQDs, respectively. The CL mechanism and the corresponding emitting species were investigated. The linear concentration range of the proposed method was 0.05–20 μM with a detection limit of 20 nM (S/N = 3). The accuracy of the proposed method was evaluated by spiking the known concentrations of the analyte and the calculated percent recoveries are in the range of 94.51–104.05% indicating the good analytical performance of the developed method.